Characterization of aerosol and assessment of the risk of transmission of SARS-COV-2 VIRUS in a natural thermal cave - Scungio Mauro (EDP Sciences, 2021)
Thermal caves represent an environment characterized by unique chemical-physical properties, often used by customers for treatment and care of musculoskeletal, respiratory and skin diseases. The recent pandemic caused by COVID-19 has imposed the need to investigate the potential transmission scenario of SARS-CoV-2 virus also in such atypical and poorly studied indoor environments. This research work was carried out inside a natural thermal cave located in Italy where a waterfall of sulfur-sulfate-bicarbonate-alkaline earth mineral thermal water creates a warm-humid environment with 100% humidity and 48°C temperature. A characterization of the aerosol was carried out in terms of number, surface area and mass, as well as particle size distributions. The physical characteristics of the aerosol were measured inside the natural thermal cave and in other immediately adjacent areas in two different days and in two distinct moments by means of an optical spectrometer. The data obtained showed a predominance of particles with a diameter greater than 8 μm, associated with a low ability of penetration in the human respiratory system. Subsequently, through a model recently proposed in scientific literature, it was evaluated the airborne transmission risk of SARS-CoV-2 inside the cave by quantifying the probability of infection due to exposure in a microenvironment in presence of a SARS-CoV-2 infected subject. The infection risk was evaluated for different scenarios obtained combining parameters such as physical, breathing or talking activities of the occupants, simultaneous or non-simultaneous access to the cave and mechanical ventilation activated or non-activated. In terms of the risk of SARS-CoV-2 infection, evaluated under the hypotheses of the model, it was highlighted the decisive effect of the mechanical ventilation system on the risk of contagion: for all the hypothesized scenarios, there is a substantial reduction in the risk of contagion considering the ventilation system active. Furthermore, the adoption of social distancing measures such as non-simultaneous access to the cave makes the risk of contagion extremely low, according to the assumptions underlying the model, even with the mechanical ventilation system not active.